Novel fabrication process of planar waveguides in rare-earth doped fluoroindate glasses - Melo, R. P. de; Silva, B. J. P. da; Falcão-Filho, E. L.; Silva, E. F. da; Petrov, D. V.; Araújo, Cid B. de; Messaddeq, Younes [UNESP]; Aegerter, M. A. (AIP Publishing, 1995)
We report the successful fabrication of planar waveguides in rare-earth doped fluoroindate glass substrates. A new procedure for waveguide fabrication using a thermally evaporated AgF nonmetallic film was developed. The refractive index changes of more than 0.03, associated to low propagation losses achieved, open new perspectives and show the potentiality of using this glass family toward further developments in fabrication and design of integrated optical devices for optical communication wavelengths.© 1995 American Institute of Physics.